"It's hard for me to tell my story" the experiences of Aboriginal and Torres Strait Islander male clients at a residential drug and alcohol rehabilitation centre using primary health care. (18th January 2021) - Farnbach, Sara; Fernando, Jamie; Coyte, Joe; Simms, Matthew; Hackett, Maree L.
Abstract: Issue addressed: Aboriginal males who use drug and alcohol may experience unique barriers accessing primary health care. This study explores the perceptions of Aboriginal males in treatment for drug and alcohol use around their experiences accessing primary health care, and barriers to access. Methods: Twenty male Aboriginal clients at a fee‐paying residential drug and alcohol rehabilitation centre completed semi‐structured interviews about their primary health care experiences before their stay. Interpretative phenomenological analysis was used to inductively develop themes. Results: About half the males had regular General Practitioners at a mainstream primary health care service or Aboriginal Medical Service. Positive experiences included having medical needs met or understanding the health information provided; and negative experiences included inefficient health service or system processes or experiencing cultural bias or racism. Barriers included limited access to appointments or to the same GP regularly, long wait times, lack of access to transport, worry or fear about their health or the visit or their complex lives taking priority. Conclusion: This research showed that the participants sought out health care and identified barriers to accessing care and potential improvements. So what?: Access to a regular General Practitioner, continuity of care and culturally appropriate and comprehensive communication techniques are important to facilitate access to primary health care by Aboriginal males. Efforts to enhance access may focus on inherent strengths within Aboriginal communities including focusing on relationships between clinicians and families, providing a welcoming environment and encouraging clients to bring a trusted family member to appointments.